2017
DOI: 10.1371/journal.pmed.1002290
|View full text |Cite
|
Sign up to set email alerts
|

First-trimester artemisinin derivatives and quinine treatments and the risk of adverse pregnancy outcomes in Africa and Asia: A meta-analysis of observational studies

Abstract: BackgroundAnimal embryotoxicity data, and the scarcity of safety data in human pregnancies, have prevented artemisinin derivatives from being recommended for malaria treatment in the first trimester except in lifesaving circumstances. We conducted a meta-analysis of prospective observational studies comparing the risk of miscarriage, stillbirth, and major congenital anomaly (primary outcomes) among first-trimester pregnancies treated with artemisinin derivatives versus quinine or no antimalarial treatment.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 44 publications
4
90
0
Order By: Relevance
“…In a meta-analysis of five studies including data from Moore et al, 2016, the risk of miscarriage was higher with first trimester quinine (incidence 5 96/945 5 10.2%) compared with all artemisinins and ACTs combined (incidence 5 37/671 5 5.5%), but the hazard ratio for the two treatments (ratio of instantaneous risk calculated using the Cox proportional hazards model) was not statistically significant (Dellicour et al, 2017). The incidences of stillbirth for the two treatments were similar (11/615 5 1.8% for quinine versus 10/654 5 1.5% for artemisinins).…”
Section: Experience In Pregnant Women In the First Trimestermentioning
confidence: 96%
See 2 more Smart Citations
“…In a meta-analysis of five studies including data from Moore et al, 2016, the risk of miscarriage was higher with first trimester quinine (incidence 5 96/945 5 10.2%) compared with all artemisinins and ACTs combined (incidence 5 37/671 5 5.5%), but the hazard ratio for the two treatments (ratio of instantaneous risk calculated using the Cox proportional hazards model) was not statistically significant (Dellicour et al, 2017). The incidences of stillbirth for the two treatments were similar (11/615 5 1.8% for quinine versus 10/654 5 1.5% for artemisinins).…”
Section: Experience In Pregnant Women In the First Trimestermentioning
confidence: 96%
“…A meta-analysis of data from six articles was conducted recently to evaluate the effects of artesunate or ACTs administered during the first trimester (Dellicour et al, 2017). There were no detectable differences between the group treated with artemisinin or ACT (n 5 717 for evaluation of the miscarriage rate and n 5 551 for major congenital anomalies) compared with the group treated with quinine (n 5 947 and 741, respectively).…”
Section: Experience In Pregnant Women In the First Trimestermentioning
confidence: 99%
See 1 more Smart Citation
“…No randomized trials evaluating AL use during the first trimester of pregnancy were found (Table 3). However, a meta-analysis of observational and other studies from six sub-Saharan African countries and the Thai-Burmese border included data from a total of 717 women taking ACTs during the first trimester of pregnancy ( 22 ). Comparisons of pregnancy outcomes between women taking ACTs and those receiving a quinine-based regimen anytime during the first trimester and treatment with ACTs versus quinine-based regimen during 6–12 weeks’ gestational age demonstrated no differences in miscarriage, stillbirth, or pregnancy loss (miscarriage and still birth combined) for women treated with ACTs versus quinine-based regimens during either period.…”
Section: Rationale and Evidencementioning
confidence: 99%
“…Comparisons of pregnancy outcomes between women taking ACTs and those receiving a quinine-based regimen anytime during the first trimester and treatment with ACTs versus quinine-based regimen during 6–12 weeks’ gestational age demonstrated no differences in miscarriage, stillbirth, or pregnancy loss (miscarriage and still birth combined) for women treated with ACTs versus quinine-based regimens during either period. Although limited by sample size, the pooled prevalences of congenital anomalies in infants born to mothers taking ACTs versus quinine-based regimens in the first trimester were similar (1.5%, 95% CI = 0.6–3.5 versus 1.2%, 95% CI = 0.6–2.4, respectively) ( 22 ). …”
Section: Rationale and Evidencementioning
confidence: 99%